2007
DOI: 10.4141/s06-053
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia emissions from land-applied beef cattle manure

Abstract: McGinn, S. M. and Sommer, S. G. 2007. Ammonia emissions from land-applied beef cattle manure. Can. J. Soil Sci. 87: [345][346][347][348][349][350][351][352] ) is emitted in vast quantities from exposed livestock manure. The volatilisation of NH 3 from livestock manure is a loss in valuable nitrogen in land-applied manure that could otherwise be used for crop production. Ammonia loss to air is also affiliated with environmental problems when it is deposited to the surrounding landscape. The goal of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…The ammonia emission rate from fields fertilized with manure slurry peaks within the first 24 h after applying the manure slurry in the field. This is probably because the volatile ammonia is already present in the manure slurry when it is applied to the field (Huijsmans et al 2001;McGinn and Sommer 2007;Rochette et al 2009;Salazar et al 2014). In contrast, the ammonia emission rate from the fields applied with synthetic urea fertilizer is more variable, and the maximum rate is not reached before 48 h to 12 days after fertilizing the field, as urea must first be hydrolyzed by the microbial urease present in the soil (Rochette et al 2009;Salazar et al 2014).…”
Section: Urine-derived Versus Synthetic Urea As Fertilizermentioning
confidence: 99%
“…The ammonia emission rate from fields fertilized with manure slurry peaks within the first 24 h after applying the manure slurry in the field. This is probably because the volatile ammonia is already present in the manure slurry when it is applied to the field (Huijsmans et al 2001;McGinn and Sommer 2007;Rochette et al 2009;Salazar et al 2014). In contrast, the ammonia emission rate from the fields applied with synthetic urea fertilizer is more variable, and the maximum rate is not reached before 48 h to 12 days after fertilizing the field, as urea must first be hydrolyzed by the microbial urease present in the soil (Rochette et al 2009;Salazar et al 2014).…”
Section: Urine-derived Versus Synthetic Urea As Fertilizermentioning
confidence: 99%
“…However, CH 4 emissions from heaps of solid manure with these alternative management measures are also (very) low, in case air temperature is relatively low (e.g. However, the mechanism behind the stockpiling-induced increase in N 2 O emission has not been well-studied and therefore requires further research (McGinn & Sommer, 2007;Sagoo et al, 2007;Shah et al, 2012). This indicates that measures to mitigate CH 4 emissions from manure heaps should be especially implemented during warm seasons.…”
Section: Stockpiling Compaction and Coveringmentioning
confidence: 99%
“…5b). However, the mechanism behind the stockpiling-induced increase in N 2 O emission has not been well-studied and therefore requires further research (McGinn & Sommer, 2007;Sagoo et al, 2007;Shah et al, 2012).…”
Section: Stockpiling Compaction and Coveringmentioning
confidence: 99%
“…Therefore, fermented manure has a smaller potential for NH 3 volatilization than fresh manure. For example, McGinn and Sommer (2007) reported that the NH 3 volatilization losses following surface applications of fresh manure and compost of beef cattle were 5.7% and 0.2% of the applied T‐N, respectively. According to McGinn and Sommer (2007), the very small loss of 0.2% of applied T‐N resulted from the application of compost with a rate of 27.7 Mg fresh weight ha −1 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, McGinn and Sommer (2007) reported that the NH 3 volatilization losses following surface applications of fresh manure and compost of beef cattle were 5.7% and 0.2% of the applied T‐N, respectively. According to McGinn and Sommer (2007), the very small loss of 0.2% of applied T‐N resulted from the application of compost with a rate of 27.7 Mg fresh weight ha −1 . Thus, it is inferred that changes in NH 3 volatilization loss would be small if the low application rates of manure in the present study, corresponding to 2.4–5.2 Mg fresh weight ha −1 , were increased to those of actual upland cropping (e.g.…”
Section: Discussionmentioning
confidence: 99%